2003
DOI: 10.1890/0012-9658(2003)084[0174:tsobrb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Boundary Regions Between Kelp Beds and Deforested Areas

Abstract: Two distinct organizational states of kelp forest communities, foliose algal assemblages and deforested barren areas, typically display sharp discontinuities. Mechanisms responsible for maintaining these state differences were studied by manipulating various features of their boundary regions. Urchins in the barren areas had significantly smaller gonads than those in adjacent kelp stands, implying that food was a limiting resource for urchins in the barrens. The abundance of drift algae and living foliose alga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(172 citation statements)
references
References 64 publications
10
161
1
Order By: Relevance
“…The increasing probability of finding sea urchins outside of the kelp bed detected in this study in all populations in spring has been shown for other kelp forests (Konar and Estes 2003). Sea urchin distribution may spread out and away from the kelp forest during increased nitrate conditions in spring when macroalgal recruitment may be greater outside of the kelp canopy due to increased light there.…”
Section: Discussionsupporting
confidence: 71%
“…The increasing probability of finding sea urchins outside of the kelp bed detected in this study in all populations in spring has been shown for other kelp forests (Konar and Estes 2003). Sea urchin distribution may spread out and away from the kelp forest during increased nitrate conditions in spring when macroalgal recruitment may be greater outside of the kelp canopy due to increased light there.…”
Section: Discussionsupporting
confidence: 71%
“…Paine & Trimble (2004) stated that the shift is evidence for multiple stable states, but it appears that the existence of hysteresis is inferred from the sudden shifts over time. Konar & Estes (2003) addressed abrupt spatial shifts in the boundary between kelps and barrens. They manipulated both kelps and urchins and provided good evidence that the presence of kelps keeps out urchins and thus sets the boundary.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…abrupt regime shifts from corals to macroalgae in tropical systems, and from macroalgae to barrens or mussel beds in temperate systems, which result in changes in abundance of exploited fish stocks (Done 1992, Hare & Mantua 2000, Konar & Estes 2003, deYoung et al 2004, Paine & Trimble 2004, Mumby 2009, Petraitis et al 2009). Ecologists are especially interested in these sudden shifts because they are common in a variety of situations, often occur unexpectedly, and are difficult to reverse.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown, by using physical models of large algae, that the movement of foliose algae by the water may restrict urchin movement (Konar and Estes, 2003). In this paper, the conse-50 quences of differential motility in different habitats will be explored, whatever its cause.…”
mentioning
confidence: 97%